Diaphragmatic Hernia After Totally Laparoscopic Total Gastrectomy for Gastric Cancer. Issue 3 (June 2019) - Gong, Chung Sik; Ko, Chang Seok; Kim, Byung Sik; Kim, Hee Sung
Abstract : This study aimed to investigate the occurrence of diaphragmatic hernia (DH) after totally laparoscopic total gastrectomy (TLTG) for gastric cancer. We reviewed retrospectively collected data from 490 consecutive patients who underwent TLTG (functional method, 365; overlap method, 125) for upper body gastric cancer, between January 2011 and May 2017, performed by a single surgeon. The median follow-up period was 40.6 months. Of 490 patients, 8 (1.63%) developed DH at a mean interval after TLTG of 7.3 (range, 3.4 to 12.8) months. All 8 patients were from the functional group, and presented with abdominal pain or vomiting. They were managed with emergency surgery (5 laparoscopic hernia reduction, 3 open hernia reduction). The grade of complication according to Clavien-Dindo classification (CDC) was CDC-III in 7 cases and CDC-IV in 1 case. There was no death associated with DH complications. None of the patients in the overlap group developed DH. The incidence of DH after TLTG is negligible in the overlap method. Therefore, the overlap method may be a safe reconstruction technique that can reduce the occurrence of DC after TLTG for gastric cancer.